Students' subjective constructions and their satisfaction with academic life - Tamara N. Dragojević; Aleksandra N. Pavlović (University of Belgrade, Teacher Education Faculty, 2024)
Students' satisfaction with academic life, which implies their overall experience at university and the quality of adaptation to academic environment, is conditioned by subjective experience. Subjective constructions of students represent the attitude of students towards the expected outcomes, motivation, commitment and effort invested in reaching the set goals. Starting from the hypothesis of the connection between students' subjective constructions and their satisfaction with academic life, empirical research was conducted which involved the students of the University of Novi Sad. The hypothesis was confirmed, given that the research results indicate that there is a statistically significant positive correlation between the satisfaction with academic life and optimism (Pearson coefficient .421**, p=.00), while there is a statistically significant negative correlation between their satisfaction with academic life and pessimism (Pearson coefficient -.291**, p=.00). In addition, statistically significant differences were found in relation to certain sociodemographic characteristics of the students. The research and understanding of the factors that affect students' satisfaction with academic life, as well as their attitudes towards the expected outcomes and the future, can contribute to the development of strategies for providing assistance and support to students in organizing life and work in the academic environment.